A Symmetrization Result for Nonlinear Elliptic Equations - Ferone, Vicenzo; Messano, Basilio (Revista Matemática Complutense, 2004)
We consider a solution u of the homogeneous Dirichlet problem for a class of nonlinear elliptic equations in the form A(u) = g(x, u) + f, where the principal term is a Leray-Lions operator defined onW1,p.